Principal Component Analysis and Exploratory Factor Analysis of the Mechanical Waves Conceptual Survey - Purwoko Haryadi Santoso; Edi Istiyono; Haryanto Haryanto (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2022)
Mechanical waves conceptual survey (MWCS) is a measurement tool established by the physics education research (PER) community to evaluate conceptual physics understanding of mechanical waves. A validation study is still needed to figure out the factor structure of MWCS using two data reduction techniques, namely exploratory factor analysis (EFA) and principal component analysis (PCA). The MWCS dataset in this paper was gathered from physics students (n = 419) from nineteen Ugandan secondary schools. The findings of this research suggested the single factor of the MWCS construct that has emerged from the dataset explored in this study. Several issues involved in the calculation of inter-item correlation within the dataset are suspected as the leading cause of the missing component solution or stable loading in the data. Moreover, there might be other issues that leave open space for future exploration. The findings reported in this paper could be the subject of further discussion in evaluating the validity of the MWCS as a research-based assessment (RBA) to measure students' conceptual understanding of wave mechanics within PER studies.